Epigenetic Regulation of a Brain-specific Glycosyltransferase N-Acetylglucosaminyltransferase-IX (GnT-IX) by Specific Chromatin Modifiers - Kizuka, Yasuhiko (American Society for Biochemistry and Molecular Biology, 2014)
Expression of glycosyltransferase genes is essential for glycosylation. However, the detailed mechanisms of how glycosyltransferase gene expression is regulated in a specific tissue or during disease progression are poorly understood. In particular, epigenetic studies of glycosyltransferase genes are limited, although epigenetic mechanisms, such as histone and DNA modifications, are central to establish tissue-specific gene expression. We previously found that epigenetic histone activation is essential for brain-specific expression of N-acetylglucosaminyltransferase-IX (GnT-IX, also designated GnT-Vb), but the mechanism of brain-specific chromatin activation around GnT-IX gene (Mgat5b) has not been clarified. To reveal the mechanisms regulating the chromatin surrounding GnT-IX, we have investigated the epigenetic factors that are specifically involved with the mouse GnT-IX locus by comparing their involvement with other glycosyltransferase loci. We first found that a histone deacetylase (HDAC) inhibitor enhanced the expression of GnT-IX but not of other glycosyltransferases tested. By overexpression and knockdown of a series of HDACs, we found that HDAC11 silenced GnT-IX. We also identified the O-GlcNAc transferase (OGT) and ten-eleven translocation-3 (TET3) complex as a specific chromatin activator of GnT-IX gene. Moreover, chromatin immunoprecipitation (ChIP) analysis in combination with OGT or TET3 knockdown showed that this OGT-TET3 complex facilitates the binding of a potent transactivator, NeuroD1, to the GnT-IX promoter, suggesting that epigenetic chromatin activation by the OGT-TET3 complex is a prerequisite for the efficient binding of NeuroD1. These results reveal a new epigenetic mechanism of brain-specific GnT-IX expression regulated by defined chromatin modifiers, providing new insights into the tissue-specific expression of glycosyltransferases.